The public relations writer's handbook - Lehmann, Whitney (Whitney S.) (Routledge, Taylor & Francis Group, 2020)
From pitches and press releases to news and feature stories to social media writing and more, this new book by author Whitney Lehmann and a handful of experienced contributors breaks down the most widely used types of public relations writing needed to become a PR pro.